sin x = 2 \sin x = 2

Algebra Level 3

Two possible values of x x satisfying sin x = 2 \sin x = 2 can be expressed as

a b π ln ( c ± d ) i \large \frac ab \pi - \ln \left( c \pm \sqrt d \right) i

where a a , b b , c c , and d d are positive integers, for which a b < 1 \left | \dfrac ab \right | < 1 , with a a and b b being coprime and d d square-free.

Find a + b + c + d a+b+c+ d .

Notations:


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Tom Engelsman
Sep 23, 2017

Let x = A + B i x = A + Bi such that s i n ( x ) = e i x e i x 2 i = 2 e i x e i x = 4 i . sin (x) = \frac{e^{ix} - e^{-ix}}{2i} = 2 \Rightarrow e^{ix} - e^{-ix} = 4i. Further substitution and simplification yields:

e i ( A + B i ) e i ( A + B i ) = e A i e B i 2 e A i e B i 2 = e B e A i e B e A i = e B ( c o s ( A ) + i s i n ( A ) ) e B ( c o s ( A ) i s i n ( A ) ) = 4 i e^{i(A+Bi)} - e^{-i(A+Bi)} = e^{Ai}e^{Bi^2} - e^{-Ai}e^{-Bi^2} = e^{-B}e^{Ai} - e^{B}e^{-Ai} = e^{-B}(cos(A) + i \cdot sin(A)) - e^{B}(cos(A) - i \cdot sin(A)) = 4i ;

which after matching the real and imaginary components gives:

e B c o s ( A ) e B c o s ( A ) = 0 e^{-B} cos(A) - e^{B} cos(A) = 0 and e B s i n ( A ) + e B s i n ( A ) = 4 e^{-B} sin(A) + e^{B} sin(A) = 4

which produces A = π 2 A = \frac{\pi}{2} and e B + e B = 4 e 2 B 4 e B + 1 = 0 e^{-B} + e^{B} = 4 \Rightarrow e^{2B} - 4e^{B} + 1 = 0 . Let u = e B u = e^{B} to obtain the quadratic u 2 4 u + 1 = 0 u = 4 ± 4 2 4 ( 1 ) ( 1 ) 2 = 4 ± 12 2 = 4 ± 2 3 2 = 2 ± 3 u^2 - 4u + 1 = 0 \Rightarrow u = \frac{4 \pm \sqrt{4^2 - 4(1)(1)}}{2} = \frac{4 \pm \sqrt{12}}{2} = \frac{4 \pm 2\sqrt{3}}{2} = 2 \pm \sqrt{3} , or B = l n ( 2 ± 3 ) . B = ln(2 \pm \sqrt{3}).

Altogether, x = A + B i = π 2 + l n ( 2 ± 3 ) i x = A + Bi = \frac{\pi}{2} + ln(2 \pm \sqrt{3}) i , which leads to 1 + 2 + 2 + 3 = 8 . 1 + 2 + 2 + 3 = \boxed{8}.

Chew-Seong Cheong
Sep 26, 2017

sin x = 2 i 2 ( e x i e x i ) = 2 e x i e x i = 4 i Multiply both sides by e i x 1 e 2 x i = 4 e x i i e 2 x i 4 e x i i 4 = 1 4 ( e x i 2 i ) 2 = 3 Take square root both sides e x i 2 i = ± 3 i e x i = ( 2 ± 3 ) i Euler’s formula: e θ i = cos θ + i sin θ e x i = ( 2 ± 3 ) e π 2 i Take natural log both sides i x = ln ( 2 ± 3 ) + π 2 i x = π 2 ln ( 2 ± 3 ) i \begin{aligned} \sin x & = 2 \\ \frac i2 \left(e^{-xi} - e^{xi}\right) & = 2 \\ e^{-xi} - e^{xi} & = - 4i & \small \color{#3D99F6} \text{Multiply both sides by }e^{ix} \\ 1 - e^{2xi} & = -4 e^{xi}i \\ e^{2xi} -4 e^{xi}i - 4 & = 1 - 4 \\ \left(e^{xi} - 2i\right)^2 & = -3 & \small \color{#3D99F6} \text{Take square root both sides} \\ e^{xi} - 2i & = \pm \sqrt 3 i \\ e^{xi} & = (2 \pm \sqrt 3)\color{#3D99F6} i & \small \color{#3D99F6} \text{Euler's formula: }e^{\theta i} = \cos \theta + i \sin \theta \\ e^{xi} & = (2 \pm \sqrt 3)\color{#3D99F6} e^{\frac \pi 2i} & \small \color{#3D99F6} \text{Take natural log both sides} \\ ix & = \ln (2\pm \sqrt 3) + \frac \pi 2 i \\ \implies x & = \frac \pi 2 - \ln (2 \pm \sqrt 3) i \end{aligned}

a + b + c + d = 1 + 2 + 2 + 3 = 8 \implies a+b+c+d = 1+2+2+3 = \boxed{8}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...